Application of cucumber green mottle mosaic virus vector as peptide presentation system - Aik, Seng Ooi; Siang, Hee Tan; Mohamed, Rosmawati; Rahman, Norsaadah; Tianwei, Lin; Ochoa, Wendy; Othman, Rofina Yasmin (Penerbit Universiti Sains Malaysia, 2004)
Recently plant viruses have been exploited as an alternative production method for pharmaceutically important peptides [1-9]. Antigenic peptides that were produced through this approach have been shown to be immunogenic.